2016
DOI: 10.18535/ijsre/v4i05.11
|View full text |Cite
|
Sign up to set email alerts
|

Study The Effect of Coal Bottom Ash And Limestone Dust as Partial Replacement of Sand and Cement

Abstract: With the tremendous increase in the population, per capita consumption of cement production has increased by many folds. This has lead to an exponential increase in the carbon dioxide levels causing extreme pollution to the environment. Necessary steps have been taken by the researchers worldwide to find alternatives to cement so as save the environment from this rising pollution. In this paper coal bottom ash [CBA] which is a by product of coal burning thermal power plant is used as partial replacement of san… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Water-cement ratio was same for all mixes. Increase in strength was found consistent up to 30% sand substitution and 5% cement substitution [26]. Ghosh et al had experimented with coal bottom ash and fly ash separately as sand substitute in different concrete mix proportions.…”
Section: Coal Ash As Constituent Materials In Envelop Constructionmentioning
confidence: 89%
See 1 more Smart Citation
“…Water-cement ratio was same for all mixes. Increase in strength was found consistent up to 30% sand substitution and 5% cement substitution [26]. Ghosh et al had experimented with coal bottom ash and fly ash separately as sand substitute in different concrete mix proportions.…”
Section: Coal Ash As Constituent Materials In Envelop Constructionmentioning
confidence: 89%
“…OPC, sand, bottom ash and stone aggregate as the concrete mix constituents were used. The results revealed that 10-30% replacement of sand by bottom ash did not adversely impact the desired strength gain in the concrete, barring some losses in workability and flexural strength parameters [13][14][15][16][17][18][19]. Another group of Researchers investigated about the suitability of fly ash and bottom ash as replacement material of cement and normal river sand utilized in concrete making.…”
Section: Coal Ash As Constituent Materials In Envelop Constructionmentioning
confidence: 99%
“…However the gradation of particles in bottom ash and sand showed some similarity, and overall, bottom ash is recommended favourably as a replacement material to sand. Abbas et al. (2016) had studied the effect of partial replacement of cement and sand by limestone dust and bottom ash respectively.…”
Section: Introductionmentioning
confidence: 99%